Desenvolvimento de método colorimétrico utilizando dispositivo portátil para a determinação de cloreto em petróleo - Holkem, Alice Penteado (2020)
In this work, a colorimetric method was developed for the determination of chloride in crude oil using a portable device based on digital images obtained with an endoscopic camera and data processing using the PhotoMetrix PRO application. The colorimetric determination followed the precipitation equilibrium between chloride, silver, and chromate ions, based on the Mohr method. Two miniaturized methods were developed for the quantitative extraction of chloride from crude oil (one using ethyl acetate as solvent and the other using demulsifier) taking to account their feasibility to the detection technique. The determination of chloride in the aqueous extract was performed inside a 2 mL microtube and the resulting color (brick-red) was captured by the endoscopic camera attached to the portable device. The data were processed in the PhotoMetrix PRO application and a multivariate calibration model of analysis was constructed using the partial least squares (PLS) method. In order to develop a simple extraction method and in agreement with green analytical chemistry (in univariate and multivariate analysis) parameters such as the type of extraction vessel (vials of 15 and 50 mL), the sample mass, the extraction time, the temperature, the use and type of solvent, in addition to the use of demulsifier and its concentration were optimized, using a shaker with orbital agitation. The parameters of the colorimetric measurement were also optimized considering the variables related to the equilibrium of the precipitation reaction (such as the molar ratio, the reaction time and the influence of pH), as well as the instrumental variables, such as the lighting, the volume of solution, the focal length and the region of interest. The optimization of the colorimetric method was performed using aqueous reference solutions and, later, the model was applied to the determination of chloride in the extracts obtained by those extraction methods that were developed (method A and method B). Quantitative chloride recoveries were obtained using 0.7 g of crude oil, with 1.05 mL of ethyl acetate and 5 mL of H2O as extracting solution, with 30 min of extraction at 55 °C (method A) or with 0.5 g of sample, 1.90% m m-¹ of demulsifier (without organic solvent) and 5 mL of H2O, with 30 min of extraction at 50 °C (method B). Methods A and B were applied to 5 samples of in natura oil with distinct characteristics and chloride determination was performed by colorimetric detection and potentiometric titration. Results were compared with reference values obtained by ASTM D 6470 or by ion chromatography (IC) after microwave-induced combustion (MIC) decomposition and no statistical difference (ANOVA) was observed. To evaluate the accuracy of the colorimetric detection, the chloride content was determined in both extracts (from method A and method B) by colorimetric detection and by potentiometric titration. Finally, the green analytical chemistry aspects for the developed protocols (extraction and colorimetric determination) were evaluated using the AGREEnness calculator metric. It was found that with the developed methods, the generation of waste was reduced by about 250%, the analytical frequency was increased by about 6 times and the generation of toxic waste was reduced by more than 1,500 times (using methods A or B), compared to the reference standard (ASTM D 6470). The protocol proved to be simple, robust and easy-to-adapt for routine analysis, adding portability and low-cost, with an instrumental limit of quantification (LOQ) of 186 mg L-¹ and method LOQ of 93 μg g-¹ (using 10 g of crude oil and final volume of 5 mL).